A review of the legal framework in shallow geothermal energy in selected European countries: Need for guidelines. (March 2020) - Tsagarakis, Konstantinos P.; Efthymiou, Loukia; Michopoulos, Apostolos; Mavragani, Amaryllis; Anđelković, Aleksandar S.; Antolini, Francesco; Bacic, Mario; Bajare, Diana; Baralis, Matteo; Bogusz, Witold; Burlon, Sébastien; Figueira, João; et al.
Abstract: Over the past years, the installations of Shallow Geothermal Energy (SGE) systems are increasing throughout Europe, and it is indicating that a specific and detailed legal framework is necessary. Towards this direction, this paper consists of an overview of legislation issues on SGE at European level, based on concise reviews from fourteen countries, i.e., Croatia, Cyprus, France, Greece, Italy, Latvia, Lithuania, Poland, Portugal, Serbia, Slovenia, Spain, Sweden, and Turkey. Said reviews discuss key national legislation as well as experts' experience in the procedure of SGE integration. Legal and technical issues are also critically discussed for all involved countries, both individually and collectively. Findings show that high diversity exists on legislation provisions as well as on regulations, standards, and institutional support amongst European countries. The latter acts as an effective barrier for the further development of the SGE market; therefore indicating the need for a common approach. Increase of awareness, need for standardization, improvement of legal framework, and administration procedures and permitting, are essential steps in moving forward and supporting the effectiveness of design, construction, maintenance, and operation of SGE systems. Highlights: We present a legislation review for SGE in 14 European Countries. There is a lack of EU legal framework regarding SGE. Common technical rules and standardization, among EU countries is one of the main legislation barriers for SGE.